DESIGNING A COLLABORATIVE MODEL FOR THE RAW MATERIAL PROCUREMENT PROCESS TO ELEVATE THE FURNITURE INDUSTRY COMPETITIVENESS - Hapsari, Chaterine Alvina Prima; Wicaksono, Purnawan Adi; Budiawan, Wiwik; Sari, Diana Puspita; Rahma, Atheea Annisa; Paramestha, Dominico Laksma (J@ti Undip: Jurnal Teknik Industri, 2023)
The furniture industry is a non-oil and gas sector that can be developed aggressively due to the abundant natural resources provided by Indonesia's forests. However, there are several issues in the wooden furniture industry, starting on the upstream supply chain, especially in the raw material procurement process. The increasing product cost because of high procurement costs could make this industry hard to compete or grow. Thus, this study proposes an improvement of raw material procurement by developing a collaborative model to minimize the total circular procurement cost in the wooden furniture industry supply chain. Adopting the collaborative model is expected to reduce the raw material procurement costs of all parties involved in the supply chain by shortening the supply chain. In addition, this study built a dynamic system model with an implementation circular supply chain concept, which focuses on regenerating the wood raw material toward zero waste. The finding is that a collaborative model could reduce the total circular procurement cost by 25% to 35% compared to the base model. A recommendation for building the terminal comes from the collaborative model. The result of this study provides a solution to elevate the furniture industry's competitiveness through cost reduction.